2021
DOI: 10.3389/fpls.2021.709817
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Quantitative Trait Loci Associated With Micronutrient Contents, Grain Quality, and Agronomic Traits in Wheat (Triticum aestivum L.)

Abstract: Comparative genomics and meta-quantitative trait loci (MQTLs) analysis are important tools for the identification of reliable and stable QTLs and functional genes controlling quantitative traits. We conducted a meta-analysis to identify the most stable QTLs for grain yield (GY), grain quality traits, and micronutrient contents in wheat. A total of 735 QTLs retrieved from 27 independent mapping populations reported in the last 13 years were used for the meta-analysis. The results showed that 449 QTLs were succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 163 publications
(189 reference statements)
0
14
0
Order By: Relevance
“…The resulting MTAs and associated genes can assist in further MAB for nutrition enhancement in wheat varieties. Recently, more than 400 QTLs associated with 70 traits (including micronutrient contents, agronomic traits, and grain quality) were identified in wheat (Shariatipour et al, 2021). Li et al (2022) identified a set of 411 GWAS-associated genes in 5 QTLs and 2722 differentially expressed genes in responsive to low N, among which OsNIGT1, LOC_Os05g45020, and LOC_Os06g43090 were three novel strong candidates identified for N-deficiency tolerance or NUE in rice.…”
Section: 1mentioning
confidence: 99%
“…The resulting MTAs and associated genes can assist in further MAB for nutrition enhancement in wheat varieties. Recently, more than 400 QTLs associated with 70 traits (including micronutrient contents, agronomic traits, and grain quality) were identified in wheat (Shariatipour et al, 2021). Li et al (2022) identified a set of 411 GWAS-associated genes in 5 QTLs and 2722 differentially expressed genes in responsive to low N, among which OsNIGT1, LOC_Os05g45020, and LOC_Os06g43090 were three novel strong candidates identified for N-deficiency tolerance or NUE in rice.…”
Section: 1mentioning
confidence: 99%
“…The candidate genes associated with wheat leaf size within the MQTL regions were identified through the analysis of transcriptome data. Given the close evolutionary relationship between Gramineae species genomes [104], candidate genes with unknown functions in the wheat genome were evaluated in the MQTL regions of our study based on their orthologous genes in the rice genome [48]. For example, eight wheat homologs for rice genes, TraesCS1D02G393900, TraesCS1D02G394000, TraesCS1D02G394100, Traes CS4B02G064000, TraesCS5B02G508800, TraesCS7A02 G059000, TraesCS7B02G484200, and TraesCS7D02G 409700 were predicted in the early study [92], which were overlapped with six MQTLs identified in the present study.…”
Section: Potential Candidate Genes Associated With Leaf Size In Meta-...mentioning
confidence: 99%
“…This map contained 14,548 markers, including SSR, DArT, SNP and other types of markers, with a total length of 4813.72 cM, ranging from 155.6 cM to 350.11 cM in the 21 linkage groups. The map was used as reference map for projection of individual QTLs identified in independent populations [48].…”
Section: Bibliographic Collection Of Qtls For Flag Leaf Size and Cons...mentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-QTL analysis (MQTL analysis) is a reliable approach for combining available data on QTLs from different mapping populations that helps to understand the genetic mechanism of quantitative characters. Shariatipour et al [ 89 ] used a meta-analysis in wheat with seven independent segregating populations to find the most durable QTLs for traits such as yield, quality characters, and micronutrient concentrations. They observed that QTLs coding for Zn and concentration were located together (57.1%), implying the possibility of simultaneous improvement of both the nutritional traits.…”
Section: Genetics and Breeding For Biofortified Wheatmentioning
confidence: 99%